Prevalence and Determinants of Obesity and Overweight in Pre- and Post-Menopausal Women in Islamshahr: a Population-based Study - G Sotoudeh; E Niyazi; Sh Khosravi; F Khajeh Nasiri; F Koohdani (Tehran University of Medical Sciences, 2010)
Background & Objective: It is essential to conduct studies on factors related to obesity in both reproductive ages and menopausal period. The aim of this study was to describe the prevalence of general and android obesity and to assess determinants of overweight in pre- and post-menopausal women. Methods & Materials: In this cross-sectional, random survey of households, about 610 women 20-65 years were recruited. Data were collected via interviews with the participants. Weight, height, waist and hip circumferences were measured as well. The Body Mass Index (BMI) and the waist to hip ratio (WHR) were calculated. Overweight and general obesity were defined as 25≤BMI<30 and BMI≥30, respectively. Android obesity was defined as WHR≥0.85. Results: The prevalence of overweight and general obesity was 90.6% in the premenopausal women and 72.6% in the post-menopausal women. About 75% and 41.9% of pre- and post-menopausal women had android obesity, respectively. Low literate post-menopausal women had significantly more general and android obesities. In addition, postmenopausal women with more parity had more android obesity. Pre-menopausal women with low literacy and housewives had significantly more general and android obesities. In addition, pre-menopausal women with more parity had less general obesity and more android obesity. In these women, android obesity was increased with age and decreased with physical activity. Conclusion: The prevalence of general and android obesities was high in Islamshahr women, especially in the post-menopausal women. This result indicates that the women have potential risks for various diseases.